Civil war in Central Europe, 1918-1921 the reconstruction of Poland - Böhler, Jochen 1969- (The greater war 1912-1923, 2018)
Civil War in Central Europe argues that Polish independence after the First World War was forged in the fires of the post-war conflicts which should be collectively referred to as the Central European Civil War (1918-1921). The ensuing violence forced those living in European border regions to decide on their national identity - German or Polish